2019
DOI: 10.1111/dmcn.14213
|View full text |Cite
|
Sign up to set email alerts
|

Executive function deficits in children born preterm or at low birthweight: a meta‐analysis

Abstract: AimTo investigate the magnitude of executive function deficits and their dependency on gestational age, sex, age at assessment, and year of birth for children born preterm and/or at low birthweight.MethodPubMed, PsychINFO, Web of Science, and ERIC were searched for studies reporting on executive functions in children born preterm/low birthweight and term controls born in 1990 and later, assessed at a mean age of 4 years or higher. Studies were included if five or more studies reported on the same executive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 117 publications
(260 reference statements)
3
53
2
6
Order By: Relevance
“…Again, GA does not seem to be the main cause of this difference. These results contrast with those obtained by other studies carried out with VPT and EPT children (Alanko et al, 2017;Leijon et al, 2018;van Houdt et al, 2019), which showed clear deficits in relation to FT children in several EFs; these results support those found by Pérez-Pereira et al (2019) with healthy PT children.…”
Section: Discussioncontrasting
confidence: 92%
“…Again, GA does not seem to be the main cause of this difference. These results contrast with those obtained by other studies carried out with VPT and EPT children (Alanko et al, 2017;Leijon et al, 2018;van Houdt et al, 2019), which showed clear deficits in relation to FT children in several EFs; these results support those found by Pérez-Pereira et al (2019) with healthy PT children.…”
Section: Discussioncontrasting
confidence: 92%
“…Very preterm birth is a risk factor for long-term neurodevelopmental sequelae. 1 , 2 Among the abilities most frequently impaired are executive functions, 3 , 4 a set of higher-order and inter-related cognitive skills, responsible for adaptive and goal-directed behavior. 5 , 6 Executive function deficits in children and adolescents born preterm have been linked to persisting structural brain alterations evident on MRI, such as white matter abnormalities and smaller volumes in subcortical structures including the caudate and thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…O destaque dado ao nascimento prematuro diz respeito não apenas à idade gestacional do bebê, mas ao peso ao nascimento e os fatores de risco decorrentes da imaturidade funcional e estrutural do organismo do pré-termo 16 . Van Houdt et al 18 verificaram através de uma revisão sistemática de outros estudos que bebês prematuros de baixo peso ao nascimento para idade gestacional, apresentam probabilidade maior de desenvolver dificuldades em tarefas executivas do que bebês prematuros com peso adequado para idade gestacional.…”
Section: Desenvolvimento Neuromotor Dos Lactentes Prematuros Com Relaunclassified